Daily Routine in Orthopedics and Traumatology - Results of a Nationwide Survey of Residents - Merschin, David; Muenzberg, M.; Stange, R.; Schuettrumpf, J. P.; Mutschler, M.; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2014)
Background: The subject orthopedics and traumatology suffers by a loss of attractiveness which results in a lack of young blood. The aim of this study of the Youth Forum of the German Society of Orthopedics and Traumatology (DGOU) is to register the working conditions of residents in orthopedics.Material and Methods: In the months September and October 2013 we performed a survey on members of the following German societies: German Society of Orthopedics and Traumatology (DGOU), German Society of Traumatology (DGU) and the German Society of Orthopedics and Orthopedic Surgery (DGOOC), (age < 40). Our questionnaire includes 15 questions.Results: We achieved 28,9% (n = 331) answered questionnaires. The mean working time per week is 55 hours. 73% of all participants do more than 5 emergency services per month. 52% are more than 3 times on duty for 24 hours. Only 13% of all residents have well ordered working hours. Normally working time is divided into three parts: one third for bureaucracy, one for operation theatre and the last for other activities (e. g. ward round). 35,6% do only one surgery per week, 12% do not perform any surgeries. An annual report is performed only in 45%. A structured concept of training only exists in 16% of all hospitals. In addition to clinical work 45% are involved in scientific projects, mostly in their spare-time. Finally 58% of all surgeons would still recommend orthopedics and traumatology.Conclusion: In order to maintain orthopedics and traumatology as an attractive it is necessary to implement flexible working time models and to reorganize and improve training-concepts.
Keywords: residency; working condition; resident shortage; youth forum